2020
DOI: 10.3390/cli8110126
|View full text |Cite
|
Sign up to set email alerts
|

Urban Overheating and Cooling Potential in Australia: An Evidence-Based Review

Abstract: Cities in Australia are experiencing unprecedented levels of urban overheating, which has caused a significant impact on the country’s socioeconomic environment. This article provides a comprehensive review on urban overheating, its impact on health, energy, economy, and the heat mitigation potential of a series of strategies in Australia. Existing studies show that the average urban heat island (UHI) intensity ranges from 1.0 °C to 13.0 °C. The magnitude of urban overheating phenomenon in Australia is determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 97 publications
0
20
0
Order By: Relevance
“…This is consistent with the findings of previous studies. For example, urban trees tend to be more effective in reducing outdoor air temperatures than other types of vertical and horizontal greenery [100][101][102][103]. However, a combination of various types of green infrastructure, such as green roofs and green walls, requires less space and also has the potential to increase the overall efficacy of beneficial impacts [46,64,[103][104][105][106].…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the findings of previous studies. For example, urban trees tend to be more effective in reducing outdoor air temperatures than other types of vertical and horizontal greenery [100][101][102][103]. However, a combination of various types of green infrastructure, such as green roofs and green walls, requires less space and also has the potential to increase the overall efficacy of beneficial impacts [46,64,[103][104][105][106].…”
Section: Discussionmentioning
confidence: 99%
“…UHI could also be worsened by the ongoing climate change, which is responsible for increasingly extreme events occurrence, more frequent heatwaves, and urban overheating [4][5][6]. In Yenneti et al (2020) [7], a collection of studies on UHI intensity in 10 different Australian cities is reported, showing that the UHI magnitude ranges between 1 and 13 • C in the investigated sites.…”
Section: Introductionmentioning
confidence: 92%
“…These facts lead to a further overheating, contributing also to the depletion of the urban environment and outdoor thermal comfort [7].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the baseline methods used here are applicable to all roof types, and these include in-situ air and surface temperature measurements, and numerical and experimental studies [34], whilst others are specific to the roof type such as CRHT modelling (Cool Roof Heat Transfer) [35], hydrological modelling of hypothetical roof greening scenarios using EPA SWMM [36], coupled hygrothermal transfer models [25] for green roofs or, in the case of evaporative roofs, specific experimental set-ups to measure thermal changes instantaneously and under the same environmental conditions for a variety of porous media, to determine optimal material characteristics [37]. Some methodologies work well for two types of roofs where similar cooling mechanisms occur, such as simulations using the Penman model [38] for both green roofs and evaporative roofs or the 'Weather Research and Forecasting Model' used to measure the benefits and efficiency of green and cool roofs [38].…”
Section: State-of-the-artmentioning
confidence: 99%